Successive Oligopolies in a Pure Exchange Economy - Lahiri, Somdeb (Journal of Reviews on Global Economics, 2012)
Abstract: In this paper we assume a market structure in which there are whole-sellers, retailers and consumers. The product sold to the consumers is initially endowed with the whole-sellers. The whole-sellers value both the product and money. The retailers are not endowed with anything at all. The retailers submit bids in units of money to the whole-sellers from the revenue earned by selling the product to the consumers. The whole-sellers offer the product to the retailers who in turn sell it to the consumers. The retailers care only for money. In this model there is a trivial equilibrium with no bids or offers being submitted. In addition we establish that a unique non-trivial equilibrium exists in which every trader participates in the market. Further, such an equilibrium is symmetric- all whole-sellers offer the same quantity of the product and all retailers bid the same quantity of money. We also obtain some comparative static results.